Charge Transport Through a Single Molecule of Trans-1-Bis-Diazofluorene [60]Fullerene - Aravena-Ponce, D; Aravena-Ponce, D (American Chemical Society, 2017)
Fullerenes have attracted interest for their possible applications in various electronic, biological, and optoelectronic devices. However, for efficient use in such devices, a suitable anchoring group has to be employed that forms well-defined and stable contacts with the electrodes. In this work, we propose a novel fullerene tetramalonate derivate functionalized with trans-1 4,5-diazafluorene anchoring groups. The conductance of single-molecule junctions, investigated in two different setups with the mechanically controlled break junction technique, reveals the formation of molecular junctions at three conductance levels. We attribute the conductance peaks to three binding modes of the anchoring groups to the gold electrodes. Density functional theory calculations confirm the existence of multiple binding configurations and calculated transmission functions are consistent with experimentally determined conductance values. © 2017 American Chemical Society.